PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU PORNOGRAFI ANAK DALAM HUKUM POSITIF INDONESIA - Rantjalobo, Stanzanusa; Azisa, Nur; Maskun, Maskun (Gorontalo Law Review, 2024)
Crimes of child pornography in Indonesia are becoming increasingly widespread and increasingly worrying. This is caused by the negligence of parents who do not supervise and provide education to children about the dangers of using the internet. So that this provides an opportunity for perpetrators of child pornography to commit all forms of unlawful acts against children as the target of perpetrators in creating child pornographic content so that the actions caused by the perpetrators must be accounted for according to the legal provisions set by the government. Even though the policies on the Pornography Law, the ITE Law, the Child Protection Law, and the Criminal Code have been stipulated by the government, it turns out that these policies are still not optimal in protecting Indonesian children from pornography crimes. This is because the concept of criminal responsibility in Indonesian positive law still uses the determination of the ability to be responsible in determining mens rea/the inner attitude of perpetrators of child pornography crimes. In addition, child pornography crimes are special crimes (Lex Specialis) so that child pornography liability needs to be studied whether child pornography crimes in the concept of criminal liability are regulated in special provisions or return to general provisions. So from these problems it is necessary to formulate the concept of criminal responsibility in Indonesian positive law, especially in dealing with perpetrators of child pornography, in order to suppress the rapid growth of these crimes and protect Indonesian children from perpetrators of child pornography.